1979
DOI: 10.1121/1.383689
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sonic plesio-velocity in a compact bone sample

Abstract: Since compact bone is demonstrably anisotropic and inhomogeneous, the measured quantities yield a plesio-velocity rather than a true sonic velocity, which makes it difficult to compare velocity measurements among several bone samples. Distribution of the plesio-velocity for 11 pairs of 2 mm thick specimens from a single mature bovine compact bone sample using 100-ns well-damped sonic pulses emitted by a 10-mHz transducer show that anisotropy exists in both axial and transverse directions and must be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…A λ/4 shift in the arrival time corresponding to a decrease in the average speed of sound was also observed during hydration. The decrease in speed of sound with hydration has been reported by others for other bones (Duck, 1990;Lees et al, 1979;Lang, 1970). Since the arrival time and transmission appear to reach a steady state, it was assumed that the skull was fully hydrated after 48 hours.…”
Section: Transcranial Insertion Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…A λ/4 shift in the arrival time corresponding to a decrease in the average speed of sound was also observed during hydration. The decrease in speed of sound with hydration has been reported by others for other bones (Duck, 1990;Lees et al, 1979;Lang, 1970). Since the arrival time and transmission appear to reach a steady state, it was assumed that the skull was fully hydrated after 48 hours.…”
Section: Transcranial Insertion Lossmentioning
confidence: 99%
“…Prior work has shown that skull preparation affects the acoustic properties of an ex vivo human skull (Lang, 1970;Fry and Barger, 1978;Lees et al, 1979). Therefore, prior to performing transcranial ADV and aberration correction, the effects of skull hydration and the gas content of the hydrating water on the ultrasound transmission were studied.…”
Section: Transcranial Insertion Lossmentioning
confidence: 99%
“…Extracellular bone tissue mass densities as determined from Eqs. (1) and (2) have been documented by Lees et al [1979aLees et al [ , 1983; Lees [1987]; Lees and Page [1992]; Lees et al [1995]; Lees [2003]; Biltz and Pellegrino [1969]; Broz et al [1995]; Gong et al [1964a]; Burns [1929]; Hammett [1925], see Tables 1-5.…”
Section: Mass and Volume Measurements -Mass Densitiesmentioning
confidence: 99%
“…The experimental data of Lees et al [1979aLees et al [ , 1995Lees et al [ , 1983; Lees [1987Lees [ , 2003; Lees and Page [1992]; Biltz and Pellegrino [1969]; Gong et al [1964a]; Burns [1929]; Hammett [1925] refer to mass density determination according to Archimedes' principle: The mass of samples with a typical size of a few millimeters is measured in air. Hence, the respective value M air refers to a state of empty vascular and lacunar pores, but with wet extracellular (ec) bone matrix.…”
Section: Mass and Volume Measurements -Mass Densitiesmentioning
confidence: 99%
See 1 more Smart Citation